THE IMPORTANCE OF FOSTERING LEGAL AWARENESS OF THE PERSONALITY OF PRISONERS IN REALISING GOOD AND RESPONSIBLE CITIZENSHIP - Wiranata, Herning Widya (PT. Altin Riset Publishing, 2025)
Coaching has an important role in realizing the purpose of correctional facilities. One of the coaching that is important in forming the foundation of the prisoner's personality is the development of legal awareness that is instilled to form a good and responsible citizen. Legal awareness coaching is implemented programmatically in various prisons in Indonesia. However, in its implementation, there are various challenges faced, one of which is overcrowding. This paper aims to find out the implementation of the legal awareness coaching program, especially in Lapas Klas IIA Kediri as the main locus amid various obstacles faced. Data collection techniques used in making research are obtained from direct observation and interviews with officers and prisoners. The results obtained in the field show that there are various efforts and innovations made by the Kediri Klas IIA Correctional Facility in fostering legal awareness, both in terms of coaching programs, as well as humanist approaches taken by officers related to instilling values, morals, and understanding of the law. Therefore, as the frontline in realizing the correctional goal, various technical implementation units must compete in innovating in realizing coaching programs, especially legal awareness in the obstacles faced such as overcrowding.